Factor affecting the blessing elements to influencing the KUIPSAS staff awareness in Islamic inheritance management - Mohamad Firdaus, Mohamed Rodzali (2021)
Based on the January 2020 report, the value on frozen inheritance asset has increased to RM 90 billion, Islamic Inheritance Management is a process that involving the Islamic inheritance managemenet with the decease family members by the Malaysian Law. The inheritance asset can be liquidated and it can be fully utilized by the heirs as well as it is able to increase the economic level of their own. This study aims to evaluate the factors that affect the blessing elements to influencing the KUIPSAS staff awareness on Islamic Inheritance Management. Theory of Planned Behavior referred as the main theory but there are other theories has been referred by the researcher to supporting the research framework such as the KAP Model, FKM Model and the indicator od blessing element. Researcher used a questionnaire as an instrument to verify the factor that affects the blessing elements to influencing that the level of awareness of Islamic Inheritance Management in Malaysia. The findings showed that, out of the three independent variables, only one strong influencer on KUIPSAS staff Islamic Inheritance Management. These studies also are aiming to provide new information for researcher especially in Islamic Inheritance Management issues in Malaysia.